MONITORING OF CATTLE’S NEСROBAСTERIOSIS IN THE AGRICULTURAL COMPANY «MAIAK» OF КOTEL’VA DISTRICT, POLTAVA REGION - Передера, С. Б.; Колотій, М. В.; Передера, Ж. О.; Щербакова, Н. С. (Scientific Progress & Innovations, 2017)
The article presents the data of the monitoring of herds of cattle animals with hooves lesion pathology in recent years in agricultural farm «Maiak». We revealed that pathology of hooves infectious character was up to 30 % of infected hooves, and in 70 % we experienced a defeat infectious diseases – necrobacteriosis. Among young cattle 8–17 months of age necrobacteriosis was observed in 2013 in 3,6 % of 406 animals, and in 2015 – 2,9 % of 617 animals. It was established that the average age of animals affected by necrobacteriosis is 6–7 years of 939 190 were patients – 20,2 %, and they are high-performance animals.